Reporting of outcomes in randomized controlled trials on nail psoriasis: a systematic review. (1st March 2018) - Busard, C.I.; Nolte, J.Y.C.; Pasch, M.C.; Spuls, P.I.
Summary: One of the important complications of the skin disease, psoriasis, is the appearance of changes in the nails. These range from the formation of small pits across the surface of the nail to painful separation of the nail plate from the underlying nail bed and disfiguring enlargement and thickening of the nail itself. Given this wide range of changes in appearance it is important that, in assessing the results of treatment, researchers can use simple, but accurate, criteria for measuring changes in psoriatic nails under treatment; these are known as core outcome sets. This study, organised by investigators from the departments of dermatology in the Universities of Amsterdam and Nijmegen in the Netherlands, surveyed 65 clinical trials focussing on nail psoriasis, all of which used assessment measures for nail changes in psoriasis, the commonest of which is called the nail psoriasis severity index. However, they found that several different methods were used in the various studies. A detailed analysis of these studies has identified a number of variations in the methods used which make the results of different treatments difficult to compare. This is particularly because there was no standard way of expressing the final scores of the severity of nail disease found in these studies and also that the different aspects of severity were rated differently. Some of these assessment scoring systems have not been validated (substantiated) either. The authors call for a rethink of the use of nail assessments in psoriasis and highlight the need to develop new methods which are sufficiently robust to stand up to close scrutiny. These should allow investigators to assess the different changes seen in the diseased nails in a standardised way, so that results of different studies can be compared. They suggest that a consensus group should be established to carry out this work.